1935
DOI: 10.1037/h0062460
|View full text |Cite
|
Sign up to set email alerts
|

The development of the reactive process from early childhood to maturity.

Abstract: Except for the pioneer study by Gilbert in 1894, 1 few attempts have been made to study developmental changes in simple reaction-time. Nevertheless the problem is one of considerable theoretical interest since the speed with which an individual is able to make a simple motor response to a perceived stimulus may fairly be regarded as a significant index to his basic level of perceptual-motor integration.In Part III of his recent book, Luria 2 describes a number of interesting experiments on the development of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
0
3

Year Published

1973
1973
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 0 publications
7
26
0
3
Order By: Relevance
“…One possible problem with these results is that in the two youngest age groups tested by Bellis, the male participants were on average more than a year older than the female participants. As long ago pointed out by Goodenough (1935), the sex difference in these two age groups could have been spuriously high because the two sexes were not well matched in age. In light of this criticism, the two ESs derived from these two age groups were deleted from the data set, and the regression analysis was rerun.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…One possible problem with these results is that in the two youngest age groups tested by Bellis, the male participants were on average more than a year older than the female participants. As long ago pointed out by Goodenough (1935), the sex difference in these two age groups could have been spuriously high because the two sexes were not well matched in age. In light of this criticism, the two ESs derived from these two age groups were deleted from the data set, and the regression analysis was rerun.…”
Section: Resultsmentioning
confidence: 92%
“…More specifically, the study report (or a study author) had to provide means and standard deviations for each sex, F or t values for statistical tests of the sex differences, or the correlations (r) between sex and RT. The second criterion eliminated a number of studies: several reported only that the sex difference was nonsignificant (Bakker, 1969;Ferris, Crook, Sathananthan, & Gershon, 1976;Keating & Bobbitt, 1978;Krupski & Boyle, 1978); two reported the means but not the standard deviations for each sex (Botwinick & Brinley, 1962;Goodenough, 1935), and one reported a significant sex difference (boys were faster) in RT, but no information on which to calculate an ES (Mitchell, Chavez, Baker, Guzman, & Azen, 1990). The third criterion was that a manual response had to be made to the imperative stimulus, but, as discussed above, the manual response did not involve a reaching movement of the arm.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…The results from the 2-sec set are of interest when they are compared with the data of Jones (1937) and Goodenough (1935). Both of those investigators used short PIs in slightly irregular series, though they were not described precisely.…”
Section: Resultsmentioning
confidence: 99%
“…they were to 13 perform under a PI distribution much like that used in the 1964 study, where PI effects had been relatively small. In addition, they were run under a second PI distribution, roughly comparable to those used by Goodenough (1935) and Jones (1937) in their developmental studies of RT, both to extend the range of observation of PI effects and to assess the representativeness of the present sample.…”
Section: Experiments Imentioning
confidence: 99%
“…Findings were consistent with the view that refractory period (RP) of an information-processing element in the central processor is longer in children than in adults. A single-channel model of information processing was proposed which could explain the inverse relationship between RT and ISI; could account for the slope differences between the RT vs IS1 curves from children and adults; and could account, in part, for the overall longer RT's of children than of adults.Numerous studies have reported that children's responses are slower than the responses of adults (Bellis, 1933;Gilbert, 1894;Goodenough, 1935;Jones, 1937;Koga & Morant, 1923). Available evidence suggests that the magnitude of this difference can be substantial in comparisons involving young children.…”
mentioning
confidence: 90%